The Effect of Quenching Methods Using Various Concentrations of Saltwater Solutions on the Hardness and Corrosion Rate of Low Carbon Steel After the Hardfacing Process - Reza febriano Armas; Muhammad Fatihuddin; Basori; Ferry Budhi Susetyo; Muhammad Yunan Hasbi; Lukman Arhami; Satrio Dwifatan Sulistio (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2026)
This study analyzes the effect of different saltwater (NaCl) concentrations in the quenching medium on the microstructure, hardness, and corrosion rate of low-carbon steel after the hardfacing process. Hardfacing was performed using a DF2A-450-R electrode, followed by rapid cooling in distilled water containing 3.5%, 7%, and 10.5% NaCl. Microstructure was observed using an Olympus BX51M optical microscope, hardness was tested by the Vickers method, and corrosion behavior was evaluated via electrochemical Open Circuit Potential (OCP) and Linear Sweep Voltammetry (LSV). The results show that higher NaCl concentrations accelerate cooling and promote a more dominant martensitic structure. The 10.5% NaCl specimen achieved the highest hardness of 582.1 HV and exhibited a more positive corrosion potential with the lowest corrosion current. Therefore, the 10.5% NaCl quenching medium provides the optimal balance between hardness improvement and corrosion resistance, making it suitable for post-hardfacing heat treatment of low-carbon steel in demanding industrial applications.